1988
DOI: 10.1037/0012-1649.24.4.552
|View full text |Cite
|
Sign up to set email alerts
|

Accelerating language development through picture book reading.

Abstract: We experimentally assessed a 1-month, home-based intervention, designed to optimize parental reading of picture books to young children. Parents in the experimental group received instructions to increase their rates of open-ended questions, function/attribute questions, and expansions; to respond appropriately to children's attempts to answer these questions; and to decrease their frequency of straight reading and questions that could be answered by pointing. Control-group parents were instructed to read in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

25
818
9
93

Year Published

1998
1998
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 1,071 publications
(980 citation statements)
references
References 35 publications
25
818
9
93
Order By: Relevance
“…Likewise, few teachers provided literacy instruction that was explicit, systematic, and purposeful. This finding is of concern as children's exposure to instruction characterized by high quality ratings -including abstract vocabulary (van Kleeck, Gillam, Hamilton, & McGrath, 1997;van Kleeck, Vander Woude, & Hammett, 2006), open-ended questions (Girolametto & Weitzman, 2002;Whitehurst et al, 1988), and explicit description of phonological structures and print concepts Justice & Ezell, 2002;van Kleeck et al, 1998) -have been linked to accelerated performance on measures of language comprehension and expression, alphabet knowledge, and phonological awareness. Although this study did not use experimental methods and consequently cannot study the linkages between teachers' participation in professional development in the fall of the year and instructional quality, it is disturbing that quality was low even after workshop training.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Likewise, few teachers provided literacy instruction that was explicit, systematic, and purposeful. This finding is of concern as children's exposure to instruction characterized by high quality ratings -including abstract vocabulary (van Kleeck, Gillam, Hamilton, & McGrath, 1997;van Kleeck, Vander Woude, & Hammett, 2006), open-ended questions (Girolametto & Weitzman, 2002;Whitehurst et al, 1988), and explicit description of phonological structures and print concepts Justice & Ezell, 2002;van Kleeck et al, 1998) -have been linked to accelerated performance on measures of language comprehension and expression, alphabet knowledge, and phonological awareness. Although this study did not use experimental methods and consequently cannot study the linkages between teachers' participation in professional development in the fall of the year and instructional quality, it is disturbing that quality was low even after workshop training.…”
Section: Discussionmentioning
confidence: 99%
“…An additional feature of high-quality literacy instruction is its purposefulness, or functionality, which refers to teachers' efforts to attach decontextualized code-based aspects of literacy instruction to meaning and comprehension (Ukrainetz, 2005). Applied studies of preschool literacy intervention have shown that increases in children's participation in classroom-based literacy experiences characterized by systematic, explicit, and purposeful experiences with print and sound can accelerate emergent literacy development (e.g., van Kleeck et al, 1998;Whitehurst et al, 1988).…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to structured language tasks, an important component of the program was based on dialogic storybook reading (developed by Whitehurst et al, 1988). Dialogic reading involves specific questioning techniques used by teachers that are directed to the child to get him or her to develop more context-independent language and to expand his or her vocabulary while jointly attending to a book.…”
Section: Interventionmentioning
confidence: 99%